Pembatasan Waktu Penyidikan terhadap Tersangka Tindak Pidana Perlindungan Anak Ditinjau dari Perspektif Perlindungan Hukum (Studi di Kepolisian Resor Pasaman Barat) - Muhammad Fariz (CV Rewang Rencang, 2025)
This research analyzes investigation time limitations for child protection crime suspects at West Pasaman Resort Police from legal protection perspective. The absence of explicit regulation regarding investigation time limits in Criminal Procedure Code creates legal uncertainty and case handling disparities. Although Police Chief Regulation Number 6 of 2019 has introduced temporal control mechanisms through SP2HP system, normative gaps still exist that potentially harm suspects' rights and hinder child victims' trauma recovery. This study concludes that investigation time limitations constitute essential legal protection to ensure efficiency, legal certainty, and prevent abuse of authority in criminal justice system.